Water hyacinth a potential source for value addition: An overview. (April 2017) - Sindhu, Raveendran; Binod, Parameswaran; Pandey, Ashok; Madhavan, Aravind; Alphonsa, Jose Anju; Vivek, Narisetty; Gnansounou, Edgard; Castro, Eulogio; Faraco, Vincenza
Graphical abstract: Highlights: Overview on the production of value added products from water hyacinth. Recent trends in water hyacinth based biorefinery. Strategies for renewable fuels from water hyacinth. Several possibilities for the generation of wealth form this weed. Targeting multiple products would improve economic viability of process. Abstract: Water hyacinth a fresh water aquatic plant is considered as a noxious weed in many parts of the world since it grows very fast and depletes nutrients and oxygen from water bodies adversely affecting the growth of both plants and animals. Hence conversion of this problematic weed to value added chemicals and fuels helps in the self-sustainability especially for developing countries. The present review discusses the various value added products and fuels which can be produced from water hyacinth, the recent research and developmental activities on the bioconversion of water hyacinth for the production of fuels and value added products as well as its possibilities and challenges in commercialization.